2020
DOI: 10.5194/isprs-archives-xliv-4-w3-2020-303-2020
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of the Domestic Wastewater Treatment Plant by Activated Sludge in the Airport Area of the City Ben Slimane (Morocco)

Abstract: Abstract. Domestic wastewater (toilet water and household water from kitchens) is evacuated in unit or separate networks to the purification station (STEP) in order to eliminate their waste; organic and mineral matter, dissolved and suspended before discharging them into the natural environment or reusing them in irrigation. The main purpose of this work is to operate the wastewater treatment plant in the Ben Slimane Airport area by using activated sludge, this process consists of destroying pollutants and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For the wastewater generated by people, the activated sludge process (ASP) is the most common method to purify these wastewaters (M. Najy et al 2020). This treatment process can remove most organic pollutants (Hartley, 2008).…”
Section: Wastewater Treatment Designmentioning
confidence: 99%
“…For the wastewater generated by people, the activated sludge process (ASP) is the most common method to purify these wastewaters (M. Najy et al 2020). This treatment process can remove most organic pollutants (Hartley, 2008).…”
Section: Wastewater Treatment Designmentioning
confidence: 99%
“…The activated sludge process has been used worldwide for the biological wastewater treatment system [1]. One of the critical steps is to separate activated sludge from liquid before discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these experiments were the complete nitrification of the wastewater, and they observed that as they were adding new samples, the process was accelerating, the new samples being nitrificated more rapidly. Further development of the wastewater treatment process has as main subject the mitigation of nitrogen by activating the sludge process [11].…”
Section: Introductionmentioning
confidence: 99%